Antimicrobial susceptibility patterns of organisms causing secondary abdominal infections in patients with perforated abdominal viscus. (July 2019) - Kumar-M, Praveen; Shafiq, Nusrat; Kumar, Pradeep; Gupta, Ashish; Malhotra, Samir; M., Naveen; Gautam, Vikas; Ray, Pallab; Gupta, Rajesh; Gupta, Vikas; Deen Yadav, Thakur; Verma, G. R.; et al.
Background: Secondary peritonitis, following intestinal perforation, constitutes a significant proportion of cases admitted as a surgical emergency and has a mortality rate of 6–21% worldwide. As a part of an antimicrobial stewardship program, we noted considerable variation among the choice of empirical regimens among such cases. Hence, we conducted a prospective study to generate the evidence for a rational empiric regimen for patients with secondary peritonitis following intestinal perforation. Methods: The study included a complete follow up of 77 cases of secondary peritonitis admitted during a 12 month period. The intraoperative fluid (peritoneal) sample of the patient was sent for culture and sensitivity pattern analysis. Results: The sites of perforation as seen in decreasing order were lower gastrointestinal (GI) (50.6%), upper GI (36.4%), and unclassified (13%). The most common organism found in the intraoperative fluid was Escherichia coli (47.9%) followed by Klebsiella pneumoniae (12.5%). amikacin, cefoperazone-sulbactam, piperacillin-tazobactam and imipenem were sensitive in 22 (out of 23 tested), 5 (out of 9), 13 (out of 13) and 22 (out of 22) isolates of E. coli and 3 (out of 6), 1 (out of 3), 4 (out of 6), 4 (out of 6) isolates of K. pneumoniae, respectively. The most common empirical antibiotic was cefoperazone-sulbactam (38.7%) followed by piperacillin-tazobactam (29.3%). Conclusion: Based on our prospective study, piperacillin-tazobactam or imipenem should be used empirically in patients presenting with complicated intra-abdominal infections secondary to perforated viscus, especially if they have sepsis or septic shock.